(untitled) (ENTHYMEMA, 2010)
Review of D. LeBlanc, Donald. Slavic Sins of the Flesh: Food, Sex, and Carnal Appetite in Nineteenth-century Russian fiction, Durham: University of New Hampshire Press, 2009. Print.